FINNSIP - The mobile Finnish Seismic Instrument Pool - Gregor Hillers; Emilia Koivisto; Päivi Haapanala; Ilmo Kukkonen; Roméo Courbis; Yinshuai Ding; Thomas Fordell; Suvi Heinonen; Niina Junno; Anssi Juntunen; Kari Komminaho; Elena Kozlovskaya; et al. (Seismica)
We report on establishing the mobile Finnish Seismic Instrument Pool (FINNSIP) that is owned and operated by Finnish academic and research institutions. The pool supports domestic and international collaborative seismic research. At the conclusion of the 2020 to 2024 build-up stage, the instrumentation includes 46 broadband seismometers and digitizers, 5 accelerometers, and 1216 and 71 Geospace and SmartSolo autonomous geophone units, respectively, making FINNSIP one of the largest and most coherent mobile seismic instrument pools in Europe in the public sector. We explain the utilization of the pool instruments and discuss the equipment, facilities, ownership and governance structure, fees, and the management and support system. Through Finland's membership in the Observatories and Research Facilities for European Seismology (ORFEUS) and the Finnish European Plate Observing System (EPOS) node, FINNSIP endorses and implements international data management standards and best practices as promoted in Europe. The importance of appropriate data and computing systems is highlighted by the ~90 TB volume of formatted data that has been collected in 25 large-N projects between October 2021 and December 2024. We summarize a checklist for building, operating, and managing this extensive seismic pool that can inform the planning and establishment of other research infrastructure.